THE PROFILE OF CAREER INTEREST TEDENCY ELECTION BASED ON THE TYPE OF STUDENTS PERSONALITY AT CLASS OF XI SENIOR HIGH SCHOOL OF BENGKULU CITY - Wulandari, Ambar Dewi; Dharmayana, I Wayan; Suprapti, Anni (TRIADIK, 2016)
Abstract: The research aimed to describe: (1) the tendency of preference career interest, (2) Personality types, (3) profile of the preference of career interest based on personality type, and (4) to test the correlation betweenthe career interest and the personality variable.the research used quantitative descriptive method. The subjects in this research were 108 students of class X IPA and IPS senior high school in Bengkulu City. The data collected using the inventory career interest inventory and personality type. The results of this reaserch are the students have different type of personality and career interests. The selection of students career interests of class XI senior high school is accordance with the type of personality of students, and there is a very high correlation between the type of personality with career interests of students. It is shown from the results of obtain hypothesis test P=0,00 then p<0,05, it is conclude there was a significant correlation between personality type with career interests.